A New Efficient Reconfiguration Approach Based on Genetic Algorithm in PV Systems - Karakose, M.; Murat, K.; Akin, E.; Parlak, K. S. (Ieee, 2014)
The purpose of reconfiguration process in PV systems is to find the connection structure of the highest amount of power obtained by the system under partial shading conditions. In this paper, a new genetic-algorithm based approach was presented for the reconfiguration. The system tries to maximize the obtained power in the same sub-module combining the ones that have the most approximate radiation value to each other between the panels exposing to partial shading. The proposed method only needs to short-circuit currents pertaining to an adaptive and fixed panel as the input parameter. So, it has a flexible structure that can work independently from the hardware features of PV panels. It creates the initial population generating random values by benefiting from short-circuit current information it receives. Based on these values, optimum connection diagram can be obtained in a short time. The most important advantage of the proposed algorithm is its applicability in PV systems including a great number of panels and the efficient results it generated in terms of the operating speed. For the test of the proposed method, test data were obtained by the help of simulation prepared in MATLAB-SIMULINK environment. Then, these received data were used in genetic algorithm based reconfiguration algorithm, and the required result was obtained. The obtained results revealed that the proposed approach yielded more efficient results in PV systems.
IEEE 23rd International Symposium on Industrial Electronics (ISIE) -- JUN 01-04, 2014 -- Istanbul, TURKEY
Keywords: Reconfiguration; genetic algorithm; PV systems; optimization